2004
DOI: 10.1016/s0925-2312(04)00032-3
|View full text |Cite
|
Sign up to set email alerts
|

Neocortical gap junction-coupled interneuron systems may induce chaotic behavior itinerant among quasi-attractors exhibiting transient synchrony

Abstract: Recent discovery of the massive presence of gap junction couplings among neocortical FS (and LTS) interneurons poses serious questions about their collective dynamical behavior, and their possible cognitive roles. We present here the theoretical possibility that a class of neurons coupled by gap junctions may emerge spatio-temporal chaos itinerant among attractors in Milnor's sense, which in turn organizes synchronous cell groups transiently. Some physiological observations from the neocortex, e.g., local fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This dynamic transition between different representations of information has been demonstrated experimentally ( Rainer et al 1999 ; Takeda and Funahashi 2002 ; Mushiake et al 2006 ), leading to the question of how neural circuits achieve the state transition. Theoretical studies have suggested that a state transition could be induced by the operation of external inputs having synchronous properties ( Salinas and Sejnowski 2000 ; Aoyagi and Aoki 2004 ; Fujii and Tsuda 2004 ; Aoki and Aoyagi 2007 ), including transient synchrony in the network ( Gutkin et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic transition between different representations of information has been demonstrated experimentally ( Rainer et al 1999 ; Takeda and Funahashi 2002 ; Mushiake et al 2006 ), leading to the question of how neural circuits achieve the state transition. Theoretical studies have suggested that a state transition could be induced by the operation of external inputs having synchronous properties ( Salinas and Sejnowski 2000 ; Aoyagi and Aoki 2004 ; Fujii and Tsuda 2004 ; Aoki and Aoyagi 2007 ), including transient synchrony in the network ( Gutkin et al 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, meaningfulness cannot be reduced to the detection of a behavioural correlate [62] [64] . The repeating activity in a network may also be considered meaningful if it allows the activation of neural elements that can be associated to other attractors, thus allowing the build-up of higher order dynamics by means of itinerancy between attractor basins and opening the way to chaotic neural dynamics [51] , [65] – [70] .…”
Section: Methodsmentioning
confidence: 99%